Pesantren As Convalescence of Children's Mental Health: A Case Study at The Asy-Syarifiy Islamic Eco-Boarding School Lumajang, East Java, Indonesia - Syarifah, Ma’isyatusy (UIN Sunan Gunung Djati Bandung, 2023)
The lockdown of Covid-19 has brought many significant changes to human routines in daily life, including for children, although now it has entered the endemic phase. The activities of children who usually go to school and play are very limited due to the lockdown so their activities are only limited at home which brings changes to the psychological state and mental health of children, such as excessive saturation, and gadget addiction. However, changes in children's mental health during the pandemic did not seem to occur much in children studying at pesantren, because teaching and learning activities at pesantren continued to run as usual, because despite the lockdown every day they still interacted with the same people. This article is descriptive qualitative research with a socio-religious approach that examines the role of pesantren in Lumajang named Asy-Syarifiy to heal mental disorders in children, and how the education system relates to the mental health of students. Data collection was carried out by involving observation, documentation, and in-depth interviews. This research found, first, some parents sent their children to the Asy-Syarifiy to deepen their religious knowledge while at the same time healing children who were stressed due to the pandemic. Second, outdoor learning methods and an eco-pesantren concept can reduce children's stress